Medical Cannabis for Chronic Noncancer Pain: A Systematic Review of Health Care Recommendations - Yaping Chang; Meng Zhu; Christopher Vannabouathong; Raman Mundi; Roland S. Chou; Mohit Bhandari (Pain Research and Management)
Purpose. Medical cannabis for patients with chronic noncancer pain (CNCP) has been the focus of numerous health care recommendations. We conducted a systematic review to identify and summarize the currently available evidence-based recommendations. Methods. We searched MEDLINE, EMBASE, PsycINFO, the Cochrane database of systematic reviews, and websites for clinical guidelines and recommendations. We summarized the type of the publications, developers, approach of health care recommendation development, year and country of publication, and conditions that were addressed. We categorized the direction and strength of each recommendation. Results. We identified 12 eligible publications. Publication years ranged from 2007 to 2019; four (33.3%) of them were published in 2018. Canada ranked first for the number of publications (n = 4, 33.3%). Most (n = 11, 92%) of the included recommendations were based on both a systematic review of the best evidence and expert consensus. All the included publications provided a recommendation supporting medical cannabis for CNCP in general and for the specific conditions of neuropathic pain, chronic pain in people living with Human Immunodeficiency Virus (HIV), and chronic abdominal pain, with detailed information sharing and comprehensive consideration of a patient’s own values and preferences. Conclusion. Clinicians can attend to the guidance currently offered, being aware that only weak recommendations are available for medical cannabis in patients with CNCP, as a third- or fourth-line therapy. Detailed discussions with patients regarding the benefits in reducing pain and potential adverse effects are required before its prescription.